Opening Opportunities : Kenya’s Electronic Single Window Connects East Africa to Global Value Chains - Sichilima, Mupelwa (International Finance Corporation, Washington, DC, 2017)
One of the most challenging experiences for businesses involved in cross bordertrade along Kenya’s border points is the clearance of imports and exports. Until 2015, the process of clearing cargo was largely manual. More than 29 different government agencies with different roles in the clearance of international trade goods required businesses to apply for and submit different sets of cargo clearance documents. The World Bank Group’s trade and competitiveness team, through the Kenya investment climate program, has supported the government of Kenya in implementing the Kenya National Electronic Single Window System, also known as the Kenya TradeNet System. This smart lesson describes the system, how it works, its accomplishments, and lessons learned along the way.